What does the Chilean Constitution say about euthanasia?. Issue 2 (18th February 2021) - Álvarez Gálvez, Íñigo
Abstract: What does the Chilean Constitution say about euthanasia? When we read the Chilean Constitution we cannot find the word "euthanasia" in the text, and there is no such thing as a right to die, therefore the answer should apparently be that the Constitution does not say anything about euthanasia and, in short, euthanasia is not allowed. However, on a second reading we can find out some statements from which we can infer another answer. My aim is to show that there is room for the acceptance of euthanasia in the Chilean Constitution, and in other similar Constitutions and international regulations in which freedom of conscience is granted.